Genetic improvement trend analysis for end-use quality characteristics among wheat cultivars of North-Western India - Gupta, Soma; Yadav, Rajbir; Gaikwad, Kiran; Kushwah, Ashutosh; Singh, Anju M.; Bainsla, Naresh Kumar (The Indian Journal of Genetics and Plant Breeding, 2016)
To test the perception among consumers in India for declining nutritional quality of wheat, the trends in enduse quality characteristics of popular wheat cultivars of North Western Plain Zone were studied. Fourteen mega varieties released since 1900 were grown in randomized block design over two years. ANOVA revealed no significant differences for nitrogen percentage in grain as well as straw, however, significant differences among the genotypes within breeding period for kernel hardness, sedimentation value and thousand kernel weights was observed. Linear regression equation for thousand kernel weight indicated a poor gain of 0.036g per year. However, the cubical polynomial regression equation significantly improved the association between kernel weight and year of release (R2 = 0.675). Similarly, cubical polynomial equation indicated continuous decline for sedimentation value with indication of some improvement in recent past. The present study therefore, clearly establishes no perceptible loss in nutritional quality. No trend was observed for flour recovery over the years. The study establishes that breeders did not deliberately modify any of the quality traits except grain plumpness and perceived changes are either not true or due to deterioration in production environment over years. GGE biplot analysis grouped HD 2967, HDCSW 16, HD 3086 along with C 591 and identified HDCSW 16 as the most ideal genotype for grain weight.